Terres agglutinées, fragments de mondes possibles : les récits brefs de science-fiction - Yves Iehl; Jean Nimis (ReS Futurae)
Short stories involving science fiction show a huge number of possible worlds. The way we "inhabit the world" is thus challenged by these fictional wiewpoints. Collections, anthologies, magazines, fanzines and digital media give access to these texts, becoming pathways to contemporary mythologies.